REKAM MEDIS: PENGGUNAAN INFORMASI MEDIS PASIEN DALAM PELAKSANAAN ASAS PERLINDUNGAN PUBLIK - Wijaya, Yudi Yasmin; Suyanto, Edy; Tanuwijaya, Fanny (Faculty of Law, Parahyangan Catholic University, 2020)
Medical records contain confidential information of patient’s medical condition and treatment given. In the public interest or for the sake of law enforcement, the confidentiality of medical records may be breached. Stake holders (patients, health workers and law enforcers) should take cognizance of what procedures and limitation exist when requesting the acquisition of medical records in the public interest. Using a juridical doctrinal method, the prevailing rules and regulation related to medical record and its breach of confidentiality shall be analysed. One important finding is that there is a dire need to seek a balance between satisfying public interest and the protection of patient’s privacy rights.